(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
The integration of authentic materials into English language teaching (ELT) has been a topic of considerable interest in recent years. This article explores the concept of authentic materials, their benefits, potential drawbacks, and effective strategies for their implementation in the English language classroom. By examining the existing literature and research, this article aims to provide educators with practical insights into how authentic materials can be used to create engaging and effective learning experiences for students.